THE INFLUENCE OF ORGANIZATIONAL CULTURE, WORK DISCIPLINE AND MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. NARAYA TELEMATIKA MALANG CITY EAST JAVA - Aprilia, Christina Faya; Handoko, Yunus; Rachmawati, Ike Kusdyah (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The telecommunications industry faces fierce competition, requiring optimal performance. PT. Naraya Telematika struggles with declining installation processes and delayed coverage expansion due to licensing issues. Research suggests that organizational culture, work discipline, and employee motivation are crucial for performance improvement. However, findings vary, indicating a research gap in their combined influence. This study examines the effects of these factors on employee performance at PT. Naraya Telematika uses a quantitative survey method with a non-probability sampling of 48 employees. Data was analyzed with multiple linear regression using SPSS version 29. Results show that while organizational culture doesn't significantly impact performance, work discipline and motivation positively and significantly do. Collectively, these factors significantly influence employee performance, highlighting the need for a comprehensive human resource management approach to enhance installation efficiency and expedite coverage expansion. Keywords: Organizational Culture; Work Discipline; Motivation; Employee Performance